Pembentukan Nilai Nasionalisme di Pondok Pesantren At-Taqwa Bekasi Melalui Materi Sejarah pada Pembelajaran Kitab Kuning - Samudra Eka Cipta; Wawan Darmawan (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2021)
Pondok Pesantren as an educational institution that teaches diniyah is also taught about nationalism. Considering, there is a lot of negative stigma in society related to the issue of radicalism that develops in boarding schools. This is what led to the weak supervision and implementation of nationalism values in boarding schools. This study discusses how the application of nationalism values in the pondok pesantren environment, especially in Pondok Pesantren At-Taqwa Bekasi and is associated with historical learning through yellow book learning materials. Including the efforts of KH Noer Alie who is also a national hero and founder of At-Taqwa Pondok Pesantren trying to teach the values of nationalism to his students. This study uses a literary approach in writing this article. The problem formulation in this article is 1) how is the pattern of education in Pondok Pesantren At-Taqwa? 2) how is KH Noer Alie's efforts in applying the values of nationalism in Pondok Pesantren At-Taqwa?, 3) what are the yellow book materials that teach the values of nationalism